2022
DOI: 10.1126/sciadv.abp9688
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the membrane interactions of phospholipase Cγ reveals key features of the active enzyme

Abstract: PLCγ enzymes are autoinhibited in resting cells and form key components of intracellular signaling that are also linked to disease development. Insights into physiological and aberrant activation of PLCγ require understanding of an active, membrane-bound form, which can hydrolyze inositol-lipid substrates. Here, we demonstrate that PLCγ1 cannot bind membranes unless the autoinhibition is disrupted. Through extensive molecular dynamics simulations and experimental evidence, we characterize membrane binding by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…PLCγ1 proteins (the wild type and S345F variant) were expressed and purified as described in Le Huray et al (31). The proteins were expressed in E. coli and purified by a combination of Ni 2+ -chelating, heparin affinity and gel filtration chromatography.…”
Section: Protein Purification and Measurement Of Plc Activity In Vitromentioning
confidence: 99%
See 2 more Smart Citations
“…PLCγ1 proteins (the wild type and S345F variant) were expressed and purified as described in Le Huray et al (31). The proteins were expressed in E. coli and purified by a combination of Ni 2+ -chelating, heparin affinity and gel filtration chromatography.…”
Section: Protein Purification and Measurement Of Plc Activity In Vitromentioning
confidence: 99%
“…PLC-catalysed hydrolysis of phosphatidylinositol incorporated in liposomes was monitored by quantifying the production of inositol phosphate (IP1) using the IPone kit (CisBio) in an endpoint assay format as described in Liu et al (17), using the following assay buffer: 20 mM HEPES.KOH, 70 mM KCl, 3 mM EGTA, 2.97 mM CaCl2, 2 mM TCEP, 50 μg/mL fatty acid-free BSA, pH 7.0. Liposomes were prepared as outlined in Le Huray et al (31) and stored at a final concentration of 2 mg/mL and were composed of 20% PS, 45% PE, 15% PC, 10% cholesterol, 5% sphingomyelin and 5 % phosphatidylinositol (PI).…”
Section: Protein Purification and Measurement Of Plc Activity In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…MD simulation studies of the PLCγ1 core domain revealed its orientation with the membrane. Mutation of the residues that were identified by the simulations to be important for the interaction of PLCγ1 core domain with the membrane reduced the binding of PLCγ1 to liposomes 22 . MD simulations have also been used to study the association of other peripheral membrane proteins to the membrane including the talin head domain (or parts of the talin head) 23 , 24 , the KRas-4B 25 and PH domains 20 .…”
Section: Introductionmentioning
confidence: 97%
“…We recently presented a dataset of high-throughput MD simulations of the interactions of 100 pleckstrin homology (PH) domains with a complex plasma membrane model, and demonstrated the capability of the simulations to correctly identify experimentally verified sites of interaction with anionic phosphoinositide lipids, and to provide insights missing from the experimental datasets (49,50). PH domains are the largest family of membrane binding protein domains present in the Pfam database (56)(57)(58).…”
Section: Introductionmentioning
confidence: 99%